The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2021
DOI: 10.1186/s13073-021-00922-x
|View full text |Cite
|
Sign up to set email alerts
|

High-grade serous tubo-ovarian cancer refined with single-cell RNA sequencing: specific cell subtypes influence survival and determine molecular subtype classification

Abstract: Background High-grade serous tubo-ovarian cancer (HGSTOC) is characterised by extensive inter- and intratumour heterogeneity, resulting in persistent therapeutic resistance and poor disease outcome. Molecular subtype classification based on bulk RNA sequencing facilitates a more accurate characterisation of this heterogeneity, but the lack of strong prognostic or predictive correlations with these subtypes currently hinders their clinical implementation. Stromal admixture profoundly affects the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
93
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 99 publications
(126 citation statements)
references
References 134 publications
5
93
0
Order By: Relevance
“…Our study describes the first comprehensive analysis of paired methylation landscapes generated by WGBS in HGSOCs and their recurrences after chemotherapy, and the first such comparison in patients with and without germline BRCA1 and BRCA2 mutations. This study highlights the molecular heterogeneity that exists in HGSOCs between patients, consistent with single-cell analyses [ 80 , 81 ], and provides evidence that this heterogeneity extends to chemoresistant, recurrent disease. We have shown that there is an absence of common methylation signatures or specific methylation biomarkers that would indicate common mechanisms and underlying biology associated with disease recurrence or chemoresistance.…”
Section: Discussionsupporting
confidence: 79%
“…Our study describes the first comprehensive analysis of paired methylation landscapes generated by WGBS in HGSOCs and their recurrences after chemotherapy, and the first such comparison in patients with and without germline BRCA1 and BRCA2 mutations. This study highlights the molecular heterogeneity that exists in HGSOCs between patients, consistent with single-cell analyses [ 80 , 81 ], and provides evidence that this heterogeneity extends to chemoresistant, recurrent disease. We have shown that there is an absence of common methylation signatures or specific methylation biomarkers that would indicate common mechanisms and underlying biology associated with disease recurrence or chemoresistance.…”
Section: Discussionsupporting
confidence: 79%
“…Very recently, data for cells from seven untreated HGSC tumours were published, and for each cluster of tumour and host cells, specific transcriptomic markers were identified. 26 We could verify in the scRNA‐Seq dataset the cell‐type specificity of the majority of TU‐selective (7/12), immune‐cell‐selective (32/43) and CAF‐selective (8/13) cytokine genes identified in the present study (Figure S16 ), supporting the conclusions drawn from our data.…”
Section: Discussionsupporting
confidence: 89%
“…Despite considerable progress over the past years, our knowledge of the intercellular signalling network operating in HGSC metastases remains fragmentary. Published systematic transcriptomic studies suitable for the development of signalling networks are limited to ascites cells, 17 , 25 and were partly performed by scRNA‐Seq, 19 , 22 , 23 , 26 which is not informative for a subset of weakly expressed genes and possesses a limited power for differential expression studies compared to bulk analyses. 27 , 28 , 29 , 30 , 31 , 32 It is also currently unclear, to which extent ascites‐derived cell types resemble their counterparts in solid tumour lesions, since unbiased omics analysis have not been described for tumour‐associated non‐immune cells from HGSC patients.…”
Section: Introductionmentioning
confidence: 99%
“…We used marker genes CD45 and EPCAM to separate the epithelial cells from stromal cells. Cells were negative for CD45 and strongly expressed EPCAM were identified as epithelial cells [ 34 , 35 ]. Cells were filtered through a seventy-millimeter cell-Strainer (BD Biosciences, San Jose, CA, USA) and centrifuged at 1200 rpm for five minutes.…”
Section: Methodsmentioning
confidence: 99%